The theoretical framework for designing desktop virtual reality-based learning environments - Chen, Chwen Jen; Seong, Chong Toh; Wan, Mohd Fauzy (Association for the Advancement of Computing in Education (AACE), 2004)
This article describes the instructional design theoretical foundation of a desktop virtual reality-based learning environment aimed at complementing the current novice driver education system in Malaysia. It provides an elaboration of how various components of the learning environment are designed to support this theoretical underpinning that fits to the new paradigm of instruction. This is followed by the suggestion of a theoretical framework that can be used to guide the design of other virtual reality-based learning environments. This framework can also act as an initial structure that is to be further refined and/or revised, as a robust model model to guide the design and development of a learning environment using this technology is still unavailable at the present time.